The Teeny-Weeny Unicorn's Great Big Wish - Harris, Shawn (New York : Alfred A. Knopf BFYR, 2025)
A tiny unicorn longing to be big takes one last chance to make his wish come true, and with a gust of lucky wind and a fairy princess, discovers an unexpected surprise.
new kids book 2025 spring.
Keywords: Size -- Fiction; Wishes -- Fiction; Unicorns -- Fiction; Fairies -- Fiction; Picture books